The Analysis Study of Effect of Acupuncture on the Treatment of Atopic Itch: A Comprehensive Systematic Review - Stephanie, Stephanie; Natalia Wijaya, Natalia Wijaya (International Medical Journal Corp. Ltd, 2024)
Background: Atopic dermatitis is a common inflammatory skin disorder characterized by recurrent eczematous lesions and severe itching. Given its chronic nature and association with persistent pruritus, exploring therapies like acupuncture may offer valuable relief and enhance patient outcomes. This systematic review aims to explore the efficacy and mechanisms of acupuncture as a treatment for atopic pruritus based on the literature of the last decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 630 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Acupuncture shows potential as a noninvasive and effective treatment for reducing pruritus and associated symptoms in patients with atopic dermatitis and other pruritic conditions. The observed benefits, such as decreased itch intensity, improved quality of life, and reduced medication use, underline its value as an adjunct therapy.